Incidence-Based versus Prevalence-Based Approaches on Measuring Disability-Adjusted Life Years for Injury - Park, Bohyun (J Korean Med Sci, 2019)
BACKGROUND: Injury represents an important aspect of disease that affects everyone at some point in their lives. To better understand and prevent these injuries, various analytical methods have been developed to assess both the magnitude and features of injury burden. In this study, we attempted to estimate the injury burden of Korea in 2014 by comparing the prevalence-based approach used by the Global Burden of Diseases (GBD) team and the World Health Organization against an alternative incidence-based approach, and to assess the different implications of these measurements. METHODS: The 10th Korean National Hospital Discharge survey data and causes of death statistics in 2014 were used as data sources. Years of life lost (YLL), years lived with disability (YLD) and disability-adjusted life years (DALYs) were calculated using both the incidence- and prevalence-based approaches. The Korean Classification of Diseases (KCD) version 5 diagnostic codes were used to classify the mechanism of injury. RESULTS: The prevalence-based injury burden tended to be higher (1,670,229 DALYs) than the incidence-based injury burden (1,544,467 DALYs). The elderly population exhibited a higher prevalence-based YLD and DALY relative to incidence-based outcomes. In order of significance, the three most common causes of injury as calculated using an incidence-based approach were road injury, fall, and self-harm, compared with a prevalence-based method, which identified self-harm, road injury, and falls as the most common injuries. CONCLUSION: An appropriate prevention program is needed for injuries with potential to cause long-lasting morbidity. Accordingly, a tailored injury-prevention strategy should be developed for each high-risk group.